Reactions of medical students to the dissecting room - Myint, Yi Yi; Tun, Ye (Faculty of Medicine, International Islamic University Malaysia, 2002)
The objective of this study was to determine the reactions of preclinical medical students from year 1 and year 2 of the International Islamic University Malaysia (IIUM) to the dissecting room. A questionnaire was distributed to 183 students (90 from year 1 and 93 from year 2) in academic year 2001-2002. The modal age of the students was 20 years (52.9%) in year 1 and 21 (60%) in year 2. The majority of the students were Malaysian (96.6% in year 1 and 96.7% in year 2) while the rest were international students. The response rate was 77.77% (70/90) from year 1 and 96.77% (90/93) from year 2 students. It was found that less than half of the students had physical symptoms on first entry to the dissecting room. The most common was dizziness (experienced by 27.1% of year 1 students and 36.7% of year 2 students). The most frequent cause of symptoms was the smell of the dissecting room (61.4% of year 1 and 34.6% of year 2 students). The most frequent method of coping with unpleasant symptoms was by relaxation (48.6% of year 1 and 44.4% of year 2 students). We found that although a majority of students expressed no untoward reaction towards the dissecting room, 17.1% of first year and 21.1% of second year students suffered the physical symptoms for over a year. The students found examinations and course workload to be more stressful than being in the dissecting room. But 4.3% of year 1 students and 9.1% of year 2 students found that the dissecting room was the most stressful place. However, the majority rated anatomy room stress from 0 (no stress) to 2 (moderate stress) on a scale from 0 to 4. The symptoms were mainly attributed to the smell of formalin. With respect to learning methods, more than 70% students stated that they used practical classes in gross anatomy and histology as a learning method.